2013
DOI: 10.1002/ange.201210259
|View full text |Cite
|
Sign up to set email alerts
|

Multiphase Intrafibrillar Mineralization of Collagen

Abstract: In the past, the two major biomineralization motifs, biosilicification and biocalcification, have been considered as two discrete processes. However, there is increasing evidece suggesting existence of an inextricable relationship between biosilica and calcium-based biominerals. [1] Recent discovery of a unique silica-chitin-aragonite biocomposite in one genus of Demosponges (Verongida) further introduces a novel mechanism of multiphase

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…After another 8 weeks, fibrils were closely packed, displaying a plywood-like interlaced pattern of fibril bundles, similar to the hierarchical organization found (Fig. 6F, bottom) (25,(33)(34)(35)(36). These characterization studies demonstrate that BAM scaffolds elicit the production of a mineralized matrix, with clear differences in terms of bone volume, mineral density, collagen content, and degree of mineralization compared to that observed with PLA.…”
Section: In Vitro Osteogenesis Enhanced By Bamsupporting
confidence: 77%
“…After another 8 weeks, fibrils were closely packed, displaying a plywood-like interlaced pattern of fibril bundles, similar to the hierarchical organization found (Fig. 6F, bottom) (25,(33)(34)(35)(36). These characterization studies demonstrate that BAM scaffolds elicit the production of a mineralized matrix, with clear differences in terms of bone volume, mineral density, collagen content, and degree of mineralization compared to that observed with PLA.…”
Section: In Vitro Osteogenesis Enhanced By Bamsupporting
confidence: 77%
“…In this way the CaP phases are deposited over the original amorphous silica phase. 24 Sodium tripolyphosphate (TPP) a linear tripolyphosphate, that has a similar structure to that of OSA, was demonstrated to induce hierarchal mineralization within selfassembling collagen brils. TPP forms ionic cross-links (ionic bridges) within collagen molecules leading to the deposition of mineral within the brils.…”
Section: Resultsmentioning
confidence: 99%
“…23−25 Other ex vivo studies have shown that with the presence of charged polymers such as poly(allylamine hydrochloride) (PAH), 26 poly(acrylic acid) (PAA), 27 or polyaspartic acid (PASP), 23,28 ACP clusters can be stabilized and facilitate the formation of oriented intrafibrillar HAP nanoplatelets. 29,30 Inspired by these findings, we suggest that a hydrogel of charged polymers loaded with a high concentration of ACP nanoclusters could be used as a precursor for bone regeneration via a biomineralization-like pathway. (CaCl 2 ), disodium hydrogen phosphate (Na 2 HPO 4 ), sodium hydroxide (NaOH), and PAA (Mw = 450 000 Da) were purchased from Sigma-Aldrich (Beijing, China).…”
Section: Introductionmentioning
confidence: 94%